1978
DOI: 10.1007/bf01406630
|View full text |Cite
|
Sign up to set email alerts
|

Axial transverse computerized tomography in 73 glioblastomas

Abstract: Among 2,600 patients, examined by computerized tomography, 404 had brain tumours, which were gliomas in 150 cases. There were 73 glioblastomas. Examination was performed according to Ambrose's method using an intravenous injection of 1 ml 60% contrast medium per kg body weight. Thus 98% of all gliomas could be demonstrated. Glioblastomas are shown in three different forms: an annular type (55%), a nodular type (18%), and a combined type (27%). Perifocal oedema is found in 88% of glioblastomas. The oedema most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Others shared this initial enthusiasm, stating that contrast enhancement on CT scans are "more accurate a prognostic sign than pathology" 7 and that the accu-racy "reached almost that of a brain slice seen at autopsy." 21 However, later investigators found only a partial correlation between contrast enhancement on CT and other imaging modalities; they also found an inconsistent relationship between contrast enhancement and histologic grade. 3 -4 - 9 In a comparison of CT scans and neuropathologic findings in 8 patients, variations in the intensity of enhancement often had no apparent correlation with local differences in vascularity, cellularity, or pleomorphism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others shared this initial enthusiasm, stating that contrast enhancement on CT scans are "more accurate a prognostic sign than pathology" 7 and that the accu-racy "reached almost that of a brain slice seen at autopsy." 21 However, later investigators found only a partial correlation between contrast enhancement on CT and other imaging modalities; they also found an inconsistent relationship between contrast enhancement and histologic grade. 3 -4 - 9 In a comparison of CT scans and neuropathologic findings in 8 patients, variations in the intensity of enhancement often had no apparent correlation with local differences in vascularity, cellularity, or pleomorphism.…”
Section: Discussionmentioning
confidence: 99%
“….2.5-11.20.21 j n low-grade astrocytomas, the pattern of contrast enhancement was most often nodular, whereas in malignant tumors, enhancement was heterogeneous or the enhanced regions were multiloculated or ring-shaped. 2 ' 810 "' 21 Butler et al 1 showed that vascularity and necrosis in supratentorial gliomas correlate with contrast enhancement. Although cellularity and pleomorphism are less closely correlated with contrast enhancement, the authors suggested that the pathologic grade of a supratentorial malignant astrocytoma can be inferred from a post-contrast CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma, CSF, and tumor samples were stored at -70°C until use. Peritumoral edema was assessed based on preoperative MRI scans, according to the Steinhoff scale [5]. After an integrated diagnosis, in accordance with the 2016 WHO Classification of Tumors of the Central Nervous System [6], patients with tumors other than GBM were excluded from the observational group.…”
Section: Methodsmentioning
confidence: 99%